SPF-CA-1.2: an enhanced version of cellular automata-based block cipher system. Issue 3 (3rd July 2021) - Achkoun, K.; Hanin, C.; Sadak, A.; Ziani, F.; Omary, F.
Abstract : In this article, an enhanced version of SPF is presented. SPF is a previously developed cellular automata-based block cipher that combines Substitution-Permutation Networks (SPN) with a Feistel scheme using key-dependent S-boxes. SPF system has satisfying cryptographic properties against attacks. However, the rule 30 used in the Feistel round function was subject to an attack by Meier and Staffelbach (MS-attack). In order to avoid this attack, a new construction of SPF, namely SPF-CA 1.2, is proposed using a new ruleset combining linear and non-linear rules. In addition, a robust and fast key scheduling algorithm is employed to improve key efficiency. Moreover, the number of rounds has been reduced while conserving the high confusion and diffusion properties of the previous version. A thorough security analysis reveals the efficiency and robustness of the proposed construction.